A Middle Eastern showcase : Qatar's 2022 World Cup - Imeson, Taylor; Mbacke, Mouslimatou; Dixon, Jess C. (London : Human Kinetics, Inc., 2016)
This case study analyses the FIFA world cup in Qatar with an emphasis on ethics.
Originally published in Imeson, T., Mbacke, M., & Dixon, J. (2016). A Middle Eastern showcase: Qatar's 2022 World Cup. Case Studies in Sport Management, 5(1), 24-30. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nationalism and sports -- Qatar